Solution-processed Bi2S3/BiVO4/TiO2 ternary heterojunction photoanode with enhanced photoelectrochemical performance - Li Xinli; Wang Sha; Wang Kunjie; Yang Jiachen; Wang Kexuan; Han Chao; Li Lihua; Yu Renhong; Zhang Yong (Nanotechnology Reviews, 2023)
TiO2 is an important component of photoelectric devices. How to broaden the light absorption of TiO2 and accelerate the separation of photo-generated electrons and holes is the focus of the current research. Building heterojunction with narrow band gap semiconductor and TiO2 is one of the important measures to improve its photoelectric performance. We prepared BiVO4/TiO2 binary heterojunction by the simple hydrothermal method and analyzed the effect of BiVO4 precursor solution concentration on the microstructure and photoelectric performance of the heterojunction. BiVO4/TiO2 binary heterojunction can effectively improve the photoelectric performance of TiO2, and the transient current density reaches 85 μA/cm2. To further boost the photocurrent of BiVO4/TiO2, Bi2S3 was in situ grown on the heterojunction to form Bi2S3/BiVO4/TiO2 ternary heterojunction. The results show that the band gap of Bi2S3/BiVO4/TiO2 composites is significantly narrowed compared with that of TiO2. The light absorption has been expanded to the visible range, and the photogenerated current density is also greatly boosted (0.514 mA/cm2). This Bi2S3/BiVO4/TiO2 ternary heterojunction accelerates the separation of photo-carriers and improves the photoelectric performance of the device. The possible transport mechanism of photo-carriers in ternary heterojunction is analyzed. The current study provides an effective strategy for in situ construction of novel multicomponent heterojunction and provides a basis for the application of Bi2S3/BiVO4/TiO2 in the optoelectronic field.